The epidemiology of free-roaming dog and cat populations in the Wellington region of New Zealand : a dissertation presented in partial fullfilment [sic] of the requirements for the degree of Master of Veterinary Studies at Massey University - Rinzin, Karma (Massey University, 2007)
We present analyses of details of dog and cat submissions to theWellington Society for the Prevention of Cruelty to Animals shelter from July 1999 to February 2006. Our aims were to document the demographic, temporal, and spatial characteristics of the free-roaming and surrendered dog and cat population in the SPCA catchment area. The motivation for this research was to identify factors determining population growth which should in turn provide a more quantitative basis for refining strategies to control the number of free-roaming dogs and cats in this area of New Zealand. Throughout the study period a total of 3992 dogs and 14343 cats were submitted to the Wellington shelter. On average, 11 dogs (range 1 – 41) and 40 cats (range 3 – 104) were presented to the shelter in any given week. Approximately one half (2065 of 3978, 52%) of the dogs and three quarters of the cats (10431 of 14323, 73%) were classified as freeroaming (that is, animals that were wild, stray, abandoned, or lost). The age structures of submitted dogs and cats were skewed towards younger age groups (< 12 months) with little difference between sexes. A higher proportion of surrendered animals were desexed (16% dogs, cats 22%) compared with those presented as free-roaming (dogs 4%, cats 15%). The number of free-roaming dogs and cats presented to the shelter each year steadily decreased from 1999 to 2005. A total of 333 free-roaming dogs and 1637 free-roaming cats were presented to the shelter in 2000, compared with 154 dogs and 1298 cats in 2005. A clear seasonal pattern was evident for cat submissions with large numbers presented to the shelter from October to May in any given year with a peak in December and January. A subset of the Wellington SPCA catchment area was defined and kernel smoothing techniques used to plot the spatial distribution of the residence of members of the public who submitted animals to the shelter throughout the study period. We found a positive relationship between the number of households submitting animals to the shelter and mesh block level deprivation index. Leslie projection matrices were used to quantify the intrinsic rate of growth of the free-roaming dog and cat population. The intrinsic rate of population growth was 0.78 (95% CI 0.56 – 0.94) for dogs and 0.98 (95% CI 0.76 – 1.16) for cats. Assuming the intensity of recruitment of animals to the shelter was constant throughout the study period these findings indicate negative growth in the free-roaming dog population and little or no growth in the free-roaming cat population. Elasticity analyses allowed us to distinguish those factors that were most influential in determining population growth. The intrinsic rate of population growth was sensitive to changes in the submission and fecundity rates of younger animals (those less than 2 years of age) with each measure being approximately equally influential in terms of the overall effect on population growth. The studies presented in this dissertation demonstrate that submission of younger animals to the shelter (with subsequent re-homing) and/or submission and desexing (with subsequent release) are equally effective techniques for limiting the growth of the freeroaming dog and cat population in theWellington region. Areas defined as socio-economically deprived should be targeted for intervention. June to September would be an appropriate time of the year to intensify control efforts, particularly for cats.
Keywords: Stray cats; Stray dogs; Feral cats; SPCA Wellington; Cat and dog population, Wellington, New Zealand